Peningkatan Karakter Jujur Melalui Kegiatan Role Play pada Anak di TK Aisyiah 4 Beringin Sakti Pagar Alam Selatan - Sulastri, Sulastri; Fahmi (Al-Athfal: Jurnal Pendidikan Anak, 2019)
The purpose of this study was to determine the honest character improvement taught at an early age at TK Aisiyah 4 in group B children in the city of Pagar Alam. The character education in the school uses the role playing method. The form of research used is Classroom Action Research. Classroom Action Research Method (PTK) used is applying the role playing method which includes several stages, namely planning (planning), action (acting), observation (observing) and reflection (reflecting). Data collection techniques use observation and documentation of student activities. Based on the results of the assessment in the first cycle, it is known that the honest character level of children is at the stage of developing (MB), namely the Achievement Level of Development of 30.27 and then increasing in the second cycle of child development achievement level of 7.54 with criteria developing hope (BSH).